PENGANGKATAN ANAK DALAM PERSPEKTIF HUKUM ISLAM - Erha Saufan Hadana Hukum Islam (Program Pascasarjana IAIN Langsa, 2019)
This research was written with the background to find out how Islamic law responds to the issue of adoption, the rights obtained by adopted children and their position in inheritance. This research is a normative juridical research based on library data. The results of the study found that adoption in the perspective of Islamic law does not recognize adoption which makes it an absolute biological child, but the fulfillment of their rights such as clothing, food and education must still be fulfilled by adoptive parents. Regarding the position in inheritance, the child does not have the right to the inheritance of the adoptive parents, but may get a will not more than one third (1/3) of the assets left behind.